Bioluminescence Imaging of Spheroids for High‐throughput Longitudinal Studies on 3D Cell Culture Models1. (28th February 2017) - Cevenini, Luca; Calabretta, Maria M.; Lopreside, Antonia; Branchini, Bruce R.; Southworth, Tara L.; Michelini, Elisa; Roda, Aldo
Abstract: Bioluminescent (BL) cell‐based assays based on two‐dimensional (2D) monolayer cell cultures represent well‐established bioanalytical tools for preclinical screening of drugs. However, cells in 2D cultures do not often reflect the morphology and functionality of living organisms, thus limiting the predictive value of 2D cell‐based assays. Conversely, 3D cell models have the capability to generate the extracellular matrix and restore cell‐to‐cell communications; thus, they are the most suitable model to mimic in vivo physiology. In this work, we developed a nondestructive real‐time BL imaging assay of spheroids for longitudinal studies on 3D cell models. A high‐throughput BL 3D cell‐based assay in micropatterned 96‐well plate format is reported. The assay performance was assessed using the transcriptional regulation of nuclear factor K beta response element in human embryonic kidney (HEK293) cells. We compared concentration–response curves for tumor necrosis factor‐ α with those obtained using conventional 2D cell cultures. One of the main advantages of this approach is the nonlysing nature of the assay, which allows for repetitive measurements on the same sample. The assay can be implemented in any laboratory equipped with basic cell culture facilities and paves the way to the development of new 3D bioluminescent cell‐based assays. Abstract : Bioluminescence imaging of 3D‐Hek293 spheroids.